Connecting Gamified Contextual Learning with Educational Outcomes: The Case of The Adventure of Rinjani - Rindu Rahmatiah; Joni Rokhmat; A. Wahab Jufri; Gunawan Gunawan; A A Sukarso (Indonesian Journal of Teacher Education, 2024)
This article investigates the pedagogical potential of the Adventure of Rinjani. These gamified contextualized science learning media are intentionally created to support the development of students' science literacy, creativity, achievement motivation, and scientific attitude. In response to the growing demand for meaningful and engaging science education, this article presents a framework developed through a comprehensive literature review and an instructional design process guided by the Dick and Carey model, which informs the game's creation. The Adventure of Rinjani game incorporates a contextual learning model, utilizing the REACT (Relating, Experiencing, Applying, Cooperating, Transferring) approach within its gameplay. The game features seven levels, each representing a distinct real ecosystem on Mount Rinjani. Before further testing and focusing on empirical implementation, this article emphasizes the design rationale, development process, and theoretical mapping of the game elements adopted in Adventure of Rinjani to the four targeted educational outcome variables. A narrative literature review is conducted to identify how gamification and contextualized learning influence each variable. The article concludes with a conceptual mind map that visually depicts the relationship between specific features of the Adventure of Rinjani and the four expected learning outcomes. This framework can serve as a foundation for future empirical research and as a reference for educators and developers who adopt or adapt contextualized learning media integrated with gamification for 21st-century science education.